Hubungan Komunikasi Terapeutik Perawat Dengan Tingkat Kepuasan Pasien Di Rumah Sakit Bhayangkara Tingkat III Manado - Gravilia Juliana Gosal; Dina Mariana Larira; Juwita M Toar (JURNAL KEPERAWATAN, 2022)
Background: Therapeutic communication is a form of interaction that nurses do to build good and trusting relationships with patients, which aims to achieve optimal health. Communication that is not implemented properly will have an impact on patient satisfaction which will affect the assessment of nurses and hospitals. The purpose of the study was to determine the relationship between therapeutic communication and patient satisfaction at Bhayangkara Hospital Level III Manado. The research method used is quantitative research, using a correlative study design with a cross-sectional study approach. The research population is patients in the inpatient room at Bhayangkara Hospital Level III Manado with a total sample of 80 respondents. The sampling technique used is purposive sampling. The results obtained in good therapeutic communication were 91.3% while not good 8.8%, and for patient satisfaction obtained 92.5% satisfied and 7.5% dissatisfied. The fisher exact test results obtained a significant value of p-value = 0.008 where the result is smaller than = 0.05. Conclusion: The results of this study indicate that there is a relationship between nurse communication and the level of patient satisfaction at Bhayangkara Hospital Level III Manado. Suggestions for nurses to continue to apply therapeutic communication and pay attention to the quality of services provided properly so that patients feel satisfied.Â